Family's Social Support and Psychological Well-Being of the Elderly in Tembalang - Desiningrum, Dinie Ratri (Faculty of Psychology, Universitas Surabaya, 2010)
Happiness and success in old age through psychological well-being, is the desire of each individual who enters late adulthood. The strength of social support from family is important. The purpose of this study was to find the relationship between social support from families and psychological well- being of the elderly. Population of the study was the elderly in Tembalang, Semarang Selatan. A purposive random sampling technique was conducted (N = 80). Methods of data collection were the Self-Administered Questionnaire was used as data collection method. Correlation in this research was calculated through product moment technique and the contributions with regression analysis technique. Results show that respondents have a good psychological well-being and feel high social support from their families. Social support from family has a high contribution to psychological well-being, with emotional support and appreciation provide a higher contribution than the other two dimensions of social support. Kebahagiaan serta kesuksesan di masa tua melalui kesejahteraan psikologis, merupakan dambaan setiap individu yang memasuki masa dewasa akhir. Kekuatan dukungan sosial dari keluarga merupakan hal yang penting. Penelitian ini bertujuan melihat hubungan antara dukungan sosial keluarga dan kesejahteraan psikologis pada para lanjut usia (lansia). Populasi penelitian adalah sejumlah lansia di Tembalang, Semarang Selatan. Sampel (N = 80) diperoleh dengan purposive random sampling. Metode pengumpulan data adalah Self-Administered Questionnaire. Korelasi dihitung dengan product moment dan kontribusi dengan teknik analisis regresi. Hasil penelitian menunjukkan bahwa responden merasakan dukungan sosial yang tinggi dari keluarganya dengan kesejahteraan psikologis yang cukup tinggi. Dukungan sosial dari keluarga memberikan kontribusi yang tinggi terhadap kesejahteraan psikologis lansia, lalu dukungan emosional dan dukungan penghargaan memberikan kontribusi yang lebih tinggi dibandingkan kedua dimensi dukungan sosial lainnya.